Textbook of hospital pharmacy - Allwood, M. C. ;Fell, J. T. (New Delhi, India : CBS Publishers & Distributors, 2010)
Role of the Hospital Pharmacist (Report of the Working Party on the Hospital Pharmaceutical Service, Chairman Sir Noel Hall; DHSS 1970). The pharmacist can no longer be regarded only as a dispenser of medicines. He has an important consultative and management role. He should be responsible for the planning of pharmaceutical services and the establishment and maintenance of safe systems of work within his department, and the collection of data on drug use.
Section I. Provision of services -- Section II. Production of medicines -- Section III. Patient services -- Section IV. Provision of information -- Index.
Includes bibliographical references and index.
Keywords: HOSPITAL SERVICES